2021
DOI: 10.1002/jcph.1954
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Switching on Pharmacokinetics of Therapeutic Biologics and Interchangeability Assessment—A Simulation Study

Abstract: The risk in terms of safety or diminished efficacy of switching between an originator biological product and a proposed interchangeable product is an important consideration for interchangeability evaluation in the regulatory framework. This simulation study evaluated the impact of several switching study design scenarios on the pharmacokinetic (PK) assessment between a virtual originator biological product and a virtual proposed interchangeable product. Our results show that (1) at least 3 switches are needed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…No information about pharmacokinetics aspects has been described in our review, because we considered efficacy, safety and immunogenicity as the main areas of concern in clinical practice after switching. However, pharmacokinetic assessment could be an important aspect when designing a switching study to evaluate interchangeability 54 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…No information about pharmacokinetics aspects has been described in our review, because we considered efficacy, safety and immunogenicity as the main areas of concern in clinical practice after switching. However, pharmacokinetic assessment could be an important aspect when designing a switching study to evaluate interchangeability 54 …”
Section: Discussionmentioning
confidence: 99%
“…However, pharmacokinetic assessment could be an important aspect when designing a switching study to evaluate interchangeability. 54 Nevertheless, the overall analysis of switching of adalimumab in different pathologies is a strength in our study, reflecting a high homogeneity of the results in terms of safety and immunogenicity among the different diseases.…”
Section: Limitationsmentioning
confidence: 90%
“…The confidence of stakeholders is essential to the success of the adoption of biosimilars. In a recent systematic review, 26 one survey showed that 6%–38% of physicians believe biosimilars and reference products are interchangeable. At the same time, another study indicated that 28% of rheumatologists feel biosimilars and reference products cannot be interchanged 27 .…”
Section: Stakeholder Viewsmentioning
confidence: 99%